2021
DOI: 10.3389/fonc.2021.718502
|View full text |Cite
|
Sign up to set email alerts
|

Translational Potential of RNA Derived From Extracellular Vesicles in Multiple Myeloma

Abstract: The cross-talk between tumour cells and stromal cells is a hallmark of multiple myeloma (MM), a blood cancer that still remains incurable despite increased knowledge of its biology and advances in its treatment. Extracellular vesicles (EVs) derived from both tumour and stromal cells have been shown to play an important role in mediating this cross-talk ultimately favouring MM progression and drug resistance. Furthermore, EVs and their content including RNA (EV-RNA) have been successfully isolated from blood an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…For example, Khani et al [ 196 ] demonstrated DC-mediated suppression of breast cancer by engineering TEVs with miR-142 and Let7i. We have recently described the utility of EVs engineered with RNA as a strategy to re-activate the immune system against cancers including myeloma [ 197 ]. Although EVs carrying RNAs, including microRNAs, hold great promise as an innovative approach in nanomedicine to fight cancer, their use in clinical practice is still limited [ 198 , 199 , 200 , 201 ].…”
Section: Translational Applications: Targeting Ev-mediated Tumor Immu...mentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Khani et al [ 196 ] demonstrated DC-mediated suppression of breast cancer by engineering TEVs with miR-142 and Let7i. We have recently described the utility of EVs engineered with RNA as a strategy to re-activate the immune system against cancers including myeloma [ 197 ]. Although EVs carrying RNAs, including microRNAs, hold great promise as an innovative approach in nanomedicine to fight cancer, their use in clinical practice is still limited [ 198 , 199 , 200 , 201 ].…”
Section: Translational Applications: Targeting Ev-mediated Tumor Immu...mentioning
confidence: 99%
“…As discussed elsewhere [ 6 , 197 ], “a lack of standardised methodologies (e.g., EV purification, quantification, labelling) and data reporting limits inter-study comparisons and the translation of EVs from bench to bedside”. This may explain the discrepancy between the large amount of published research on the role of EVs in the tumor immune microenvironment and the few applications in clinical trial settings.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…EVs present similar biomarkers of their cell of origin, and this allows for evaluating them as a useful target for identification and treatment of cancer patients [ 118 ]. Relevantly, EVs defend their cargo including RNAs from destruction in the extracellular space and can be efficaciously isolated from peripheral blood, making them perfect elements for LB [ 119 , 120 ].…”
Section: Liquid Biopsy and Exosomesmentioning
confidence: 99%